Aerospace series. Steel X5CrNiCuNb16-4 (1.4549 type 1.4542). As cast. Reference heat treatment: homogenised, solution treated, precipitation hardened and sub zero. Remelting stock. (17th December 2019) - British Standards Institution,
No abstract available